Application Of Okra (Abelmoschus Esculentus) Mucilage-Based As Natural Coagulant In Domestic Wastewater Treatment - Ong, Kai Qi (Universiti Sains Malaysia, 2022)
This research investigates water treated extraction (AEaqs) of carbohydrate coagulants from okra (Abelmoschus esculentus) and inspects its chemical characteristics (i.e. isoelectric point (IEP) and Fourier Transform Infrared). AEaqs serves as anionic coagulants to boost bridging mechanisms by carboxyl (C=O) and hydroxyl functional groups (OH). The ability of AEaqs extract to behave as primary coagulant and coagulants aid together with alum was evaluated using the domestic wastewater collected from oxidation pond of treatment plant in the Engineering Campus of Universiti Sains Malaysia. The parameters analysed in domestic wastewater was below the limits set in Standard B, Environmental Quality (sewage) Regulation 2009, Malaysia. Jar test results were analysed according to the removal percentage of turbidity, suspended solids (SS), COD and zinc (Zn2+). In addition, the optimum conditions (pH and dosage), coagulation mechanism and floc structure were also explored. Results had shown that 20 mg/L AEaqs at pH 12 achieved 54%, 59%, 53% and 21% of turbidity, SS, COD and Zn2+ removals from its initial values of 23.14 NTU, 34 mg/L, 187 mg/L and 0.14 mg/L respectively. On the other hand, 30 mg/L alum at pH 6 removed 99%, 100%, 44% and 36% of turbidity, SS, COD and Zn2+ removals respectively. As coagulant aids, 30 mg/L alum + 2 mg/L AEaqs at pH 6 gained the highest removal in domestic wastewater sample of turbidity, SS, COD and Zn2+ with 32%, 18%, 64%, 14% respectively. A 50% reduction in the concentration of alum from its optimal dosage with doses of AEaqs (15 mg/L alum + 5 mg/L AEaqs) managed to remove -51%, -76%, 39%, 21% of turbidity, SS, COD and Zn2+. The overall removal rates for AEaqs as primary coagulant and coagulant aid were lower as compared to when alum was used alone.